Hole-mask lithography for fabricating bielement nanoplasmonic metasurfaces - Ottedag, Harald (My University, 2018)
Hole-mask colloidal lithography (HCL) has been used extensively to fabricate arrays of nanostructures with uniform physicochemical traits, e.g. in size, shape and material, on a surface. A new way to create a metasurface with nanostructures with more than one physiochemical trait, for instance both gold and silver, each with di erent dimensions and/or aspect ratio, is suggested and tried. The possible applications of such a surface lies in the eld of plasmonics for both fundamental and application aspects such as probing two di erent processes simultaneously, for instance temperature change and adsorption of molecules onto the surface. In this thesis the fabrications were unsuccessful in creating such a device, but signi cant progress was made in developing the method. Furthermore, characterisation of dual-size surfaces fabricated through HCL comprising silver discs was done. Speci cally the relationship between mean center-tocenter distance between nanoantennas, and plasmonic resonance wavelength was investigated.
Keywords: Fysik; Physical Sciences